IMPLEMENTATION MULTIMEDIA DEVELOPMENT LIFE CYCLE IN INTERACTIVE MULTIMEDIA DESIGN FOR TRADITIONAL INDONESIAN MUSIC INSTRUMENTS INTRODUCTION - Aditya Imam Zuhdi; Zahrotul Mustafidah; Muhammad Risqi Nur Alam; Safira Anggraini Irawan (JIKO (Jurnal Informatika dan Komputer), 2024)
This research aims to address the lack of interactive multimedia-based educational media in introducing traditional Indonesian musical instruments to the public, especially children. The issue arises from the fact that the diversity of traditional musical instruments in Indonesia has not been presented attractively in an interactive media format. Therefore, this study utilizes the Multimedia Development Life Cycle (MDLC) method as a guide in designing and developing interactive multimedia. The MDLC stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution, are implemented to ensure that each step of the system development is well-organized. The results of alpha testing indicate that all features of the interactive multimedia work well. Beta testing, involving 36 respondents, yields a rating of 4.52 out of 5, demonstrating that this interactive multimedia is excellent and suitable for use as a learning media for traditional Indonesian musical instruments. This research addresses the gaps in the presentation of educational information by providing an interesting and effective media, especially in the context of traditional musical instruments. Thus, it is expected that this interactive multimedia can enrich the knowledge of the public, especially children, about the cultural wealth of traditional Indonesian musical instruments.